Plants under stress by parasitic plants. (August 2017) - Hegenauer, Volker; Körner, Max; Albert, Markus
Highlights: Plant parasites attach to host plants and penetrate them by haustoria. They thieve water, solutes and carbohydrates by mimicking an attractive sink for the host. In most cases parasitic plants stay unrecognized by the host. A few host exceptions exist which display active defenses against the plant invaders. Abstract : In addition to other biotic stresses, parasitic plants pose an additional threat to plants and cause crop losses, worldwide. Plant parasites directly connect to the vasculature of host plants thereby stealing water, nutrients, and carbohydrates consequently leading to tremendously reduced biomass and losses in seed yields of the infected host plants. Initial steps to understand the molecular resistance mechanisms and the successes in ancient and recent breeding efforts will provide fundamental knowledge to further generate crop plants that will resist attacks by plant parasites.